All Days 2009
DOI: 10.2523/iptc-13765-ms
|View full text |Cite
|
Sign up to set email alerts
|

Successful Field Application of an Inhibitor Concentration Detection System in Optimising the Kinetic Hydrate Inhibitor (KHI) Injection Rates and Reducing the Risks Associated with Hydrate Blockage

Abstract: TX 75083-3836, U.S.A., fax +1-972-952-9435. AbstractCurrently, hydrate inhibitors are injected at the pipelines upstream based on the calculated/measured hydrate phase boundary, water cut, worst pressure and temperature conditions, and the amount of inhibitor lost to non-aqueous phases. In general, no means of controlling and monitoring are available along the pipeline and/or downstream to assess the degree of inhibition. Often high safety margins are considered to accommodate for the uncertainties in the abov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…Many oil and gas operations meet the conditions needed for gas hydrate formation to occur. Gas hydrate formation can jeopardize oil and gas production if not treated. One way of treating gas hydrates is by the utilization of low-dosage hydrate inhibitors (LDHIs) and, more specifically, the subgroup kinetic hydrate inhibitors (KHIs) …”
Section: Introductionmentioning
confidence: 99%
“…Many oil and gas operations meet the conditions needed for gas hydrate formation to occur. Gas hydrate formation can jeopardize oil and gas production if not treated. One way of treating gas hydrates is by the utilization of low-dosage hydrate inhibitors (LDHIs) and, more specifically, the subgroup kinetic hydrate inhibitors (KHIs) …”
Section: Introductionmentioning
confidence: 99%
“…The field evaluations of the C-V technique were in various applications such as monitoring of MeOH and MEG injection rates, measuring high MEG concentrations for MEG regeneration units, and monitoring KHI concentrations in pipelines. Lavallie et al (2009) reported the evaluation results in Dolphin Energy and suggested that the C-V device is a simple and reliable device for measuring KHI concentrations compared to conventional chemical analysis method.…”
Section: Evaluation Of the Prototype C-v Devicementioning
confidence: 99%
“…In gas hydrates, gases of certain molecular weight stabilize hydrogen-bonded molecular water cages. Thus, if suitable low-molecular weight hydrocarbon gases combine with water under specific conditions of temperature and pressure, typically favoring conditions at temperature and pressure in the ranges of <25 °C and >30 bar, respectively, gas hydrates will form. These requirements are not uncommon to encounter when producing or transporting oil and gas, and if it is left untreated, formation of gas hydrate plugs can occur, potentially jeopardizing operations and posing health hazards. Therefore, it is important to treat the system in such a manner that the risk for forming gas hydrate plugs is eliminated. There exist multiple measures to handle and treat gas hydrate; one of them is the utilization of chemicals, more specifically, low-dosage hydrate inhibitors (LDHIs) and subgroup kinetic hydrate inhibitors (KHIs) …”
Section: Introductionmentioning
confidence: 99%